(untitled) (Research, Society and Development, 2021)
Brazilian poultry farming has been evolving every year, which has also led to serious problems related to pest insects, such as Alphitobius diaperinus. The objective of this study was to evaluate the effect of the bioinsecticidal action of kaolin and mast powder for the control of Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae) on aviary bed in laboratory. The efficiency of kaolin powder was calculated by the method of Abbott (1925). The potential of the powder to repel A. diaperinus was evaluated by the Repellency Index (IR). For the association of kaolin powder and mast, the repellency index was also verified and the lowest dose of kaolin powder was used, which proved to be more efficient and economical. Also, the efficiency of the association was evaluated under the same conditions previously tested. According to the results, it can be concluded that kaolin powder at a concentration of 0.50 g/cm2 was more efficient with an efficiency of 59.86% at seven days and 100% at 21 days of the evaluated periods. It was also found that the Repellency Index obtained in the treatments with the use of kaolin varied from 0.25 to 0.75 g/cm2 and were all less than 1, indicating repellency of these concentrations. It was also found that the IR in the treatments of the lowest dose of kaolin associated with the concentrations of the mast were all less than 1, indicating repellency on the insects of A. diaperinus. As for the efficiency of the association, it was found that the concentration of 0.50 g/cm2 of the kaolin powder associated with 1.00 g/cm2 was the most efficient in controlling Alphitobius diaperinus.